Akuntansi Perbankan Syariah pada SMK LP3 Istana Jakarta Selatan - Rahmi, Mira; Priyanto, Toni; Gunaedi Argo, Jenji (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2017)
Vocational high school (SMK) is design to set student ready to work after their finish their senior educational level. However, the current curriculum of SMK not yet design for the sharia competency. In reality, lack of knowledge of sharia were exist on students and also the teachers. Huge demand in sharia industry is not an issue for vocational high school due to the lack system and human resources. One of solution that are given by FEB UPN